(NoB]ESTWENNYJ STROJ QKUTOW (BXVII-XVIII (NWW(B. / s - (NtOKAREW(B, (NsERGEJ aLEKSANDROWI^ s; (NnAU^NO(B-(NISSLEDOWATELXSKIJ INSTITUT QZYKA(B, (NLITERATURY I ISTORII qassr(B.s ((NqKUTSK (B: s (NqKUT(B. (NGOS(B. (NIZD(B-(NWO(B,s, 1945)
(Nw KONCE TEKSTA REZ@ME NA ANGL(B. (NI QKUT(B. (NQZ(B. s
(NuKAZATELI(B: (NSTR(B. 395-407 s
Keywords: (NiSTORIQs -- (NqKUTSKAQ assrs -- XVII-XVIII (NWW(B.s